Comparison of thoracic kyphosis in two groups of elite Greco-Roman and freestyle wrestlers and a group of non-athletic participants - Rajabi, R.; Doherty, P.; Goodarzi, M.; Hemayattalab, R. (British Journal of Sports Medicine, 2008)
Background: Freestyle and Greco-Roman are two types of wrestling that place the spine of athletes in different positions. Theoretically, it can be argued that this can lead to adverse effects on the spine and might be an important factor associated with changes in the degree of kyphosis.